-10x + 15y -30z + 50
The given expression is
-5(2x – 3y + 6z – 10). It has three different variables, x, y and z.
In order to simplify this expression, we will multiply each term inside the parentheses one after the other with the term outside the parentheses. The positive and negative signs will be taken into cognisance.( - - = + , + - = - , - × - = + and - × + = -) Applying the above explanation, it becomes
-5(2x – 3y + 6z – 10).
(-5×2x) +(-5×-3y) + (-5×6z) + (-5×-10)
= -10x + 15y -30z + 50
multiply -5 to everything in parentheses